Who was Coretta Scott King? - Herman, Gail, 1959- (Who was-- ?, 2018)
Presents the life and achievements of Coretta Scott King, discussing her vital role in the Civil Rights Movement, her awareness campaigns, and her efforts to continue the work of her husband, Martin Luther King, Jr.